Nastajanje ksilemske in floemske branike pri bukvah, poškodovanih v žledolomu - Merela, Maks (Acta silvae et ligni, 2016)
After the severe ice storm in 2014, numerous damaged trees were not removed from forests. Due to the lack of general knowledge about the processes occurring in damaged trees, a study involving 14 European beeches was conducted in the Arboretum Volčji Potok. Trees were categorized by crown injury; injury class K % undamaged, A % damaged less than 50 %, B % damaged between 50 and 75 %, and C % damaged more than 75 %. During the 2014 growing season, micro-cores were collected every fortnight using a Trephor tool. Changes in crowns were also observed and noted. Transverse sections of micro-cores were prepared and observed using light microscopy and an image analysis system. Xylem growth rings were 20 to 95 % narrower in damaged beech trees compared to the undamaged trees. Damaged trees also produced narrower phloem rings. The biggest differences in cambial activity in beech appeared between Class A and Class B.
Keywords: bukev; Fagus sylvatica; beech; žledolom; poškodbe krošnje; ice storm; nastajanje lesa; crown injury; ksilem; wood formation; xylem; kambij; cambium; Trephor